Epigenetic-Mediated Downregulation of μ-Protocadherin in Colorectal Tumours - Bujko Mateusz; Kober Paulina; Statkiewicz Małgorzata; Mikula Michal; Ligaj Marcin; Zwierzchowski Lech; Ostrowski Jerzy; Siedlecki Janusz Aleksander (Gastroenterology Research and Practice)
Carcinogenesis involves altered cellular interaction and tissue morphology that partly arise from aberrant expression of cadherins. Mucin-like protocadherin is implicated in intercellular adhesion and its expression was found decreased in colorectal cancer (CRC). This study has compared MUPCDH (CDHR5) expression in three key types of colorectal tissue samples, for normal mucosa, adenoma, and carcinoma. A gradual decrease of mRNA levels and protein expression was observed in progressive stages of colorectal carcinogenesis which are consistent with reports of increasing MUPCDH 5′ promoter region DNA methylation. High MUPCDH methylation was also observed in HCT116 and SW480 CRC cell lines that revealed low gene expression levels compared to COLO205 and HT29 cell lines which lack DNA methylation at the MUPCDH locus. Furthermore, HCT116 and SW480 showed lower levels of RNA polymerase II and histone H3 lysine 4 trimethylation (H3K4me3) as well as higher levels of H3K27 trimethylation at the MUPCDH promoter. MUPCDH expression was however restored in HCT116 and SW480 cells in the presence of 5-Aza-2′-deoxycytidine (DNA methyltransferase inhibitor). Results indicate that μ-protocadherin downregulation occurs during early stages of tumourigenesis and progression into the adenoma-carcinoma sequence. Epigenetic mechanisms are involved in this silencing.